CD-atlas of ophthalmology - Ford, Sue; Ronald Marsh (London ; Philadelphia : Mosby, 1998)
(Producer) Covers the whole spectrum of ophthalmic disorders. Thousands of high-quality photographs show variations in the presentation of common conditions and include numerous examples of many rarer disorders. Details of patient history, examination, investigations, and diagnosis accompany the illustrations.
Koleksi Multimedia Perp. Perubatan
Keywords: Eye Diseases -- atlases -- CD-ROM